EFFECT OF PYROLYSIS TEMPERATURES ON COMPOSITION AND ELECTRICAL CONDUCTIVITY OF CARBOSIL PREPARED FROM RICE HUSK - Wasinton Simanjuntak; Simon Sembiring; Kerista Sebayang (Universitas Gadjah Mada, 2012)
The objective of this study was to evaluate the effect of pyrolysis temperatures on composition and electrical conductivity of carbosil produced from rice husk, by conducting pyrolysis experiments at three different temperatures of 200; 400; and 700 °C. The structure of the samples was characterized using Fourier Transform Infrared (FTIR) Spectroscopy and X-Ray Diffraction (XRD). The microstructure and elemental composition were characterized using Scanning Electron Microscopy/Energy Dispersive Spectroscopy (SEM/EDS), and the electrical conductivity was measured using four probe method. The FTIR analyses revealed the existence of Si-O-Si and Si-OH functional groups, but no functional groups associated with carbon, confirming the formation of carbosil. This formation of carbosil is also supported by the results of EDS analyses which show the presence of only three elements of C, O, and Si, respectively. The XRD results indicate that the carbosils are amorphous, suggesting that no transformation of carbon and silica into crystalline phase to the limit of the temperatures applied. The carbosil formation decreased with increasing of pyrolysis temperature. The microstructure of the carbosils indicates that the higher the temperature, the smaller the grain size of the samples. The values of electrical conductivity of the samples are in the range of 1.13 x 10-3 to 6.81 x 10-3/(Ω.m) with the application of 10 tones compression pressure, but the conductivities of the sample prepared at 200 °C were found to increase with increased compression pressure to six fold from 6.81 x 10-3 to 41.94 x 10-3/(Ω.m) by increasing compression pressure to 80 tones. Based on these conductivity values, the samples are considered as semiconductor, suggesting the potential use of the carbosil in semiconductor devices.